Gesellschaften im Wandel : funerärer aufwand und soziale wirklichkeit im frühstaatlichen Mesopotamien und Ägypten anhand von Grabbefunden aus Ur und Kafr Tarkhan - Janssen, Ursula (Schriften zur vorderasiatischen Archäologie, 2015)
This study compares the representation of social stratification in the burial customs of southern Mesopotamia and Egypt in the Early Dynastic period, during the transition from the 4th to the 3rd millennium B.C. The cemeteries of Ur in southern Mesopotamia and Tarkhan in Middle Egypt, each the largest known cemetery of its time in its region, serve as the basis for material evidence. An analysis of societal differences and different uses of funerary symbols, especially those pertaining to the afterlife realms of each culture, can explain social constructions in these two regions.